PERANCANGAN DAN PEMANFAATAN TEKNOLOGI HIDROPONIK VERTIKAL HIDRO 40 HOLE BAGI KARANG TARUNA TRI TUNGGAL DI DESA TALANG PAUH - Halauddin Halauddin; Supiyati Supiyati; Suhendra Suhendra (Universitas Bengkulu, 2018)
It has been devoted an activity in community in application of science and technology with the title: Design and Utilization Hydroponic Vertical Hydro 40 Hole for Karang Taruna Tri Tunggal in Talang Pauh Village, Pondok Kelapa District, Central Bengkulu. This dedication destination to design and utilize hydroponic vertical hydro technology as one of the ground breaking technological break throughs in rural areas to complement the vegetable needs for house hold scale. From the results of the implementation of dedication can be concluded that hydroponic technology vertical model of 40 holes hydro can be well received by the participant’s devotion. The plant species are mustard, this plant can grow well from two weeks old, although the harvest period for mustard plants is estimated to 35-50 days. Keywords: hydroponic, vertical hydro, 40 hole, house hold scale, Talang Pauh Village